Strategi Pengembangan Program Kampung Iklim di Desa Sidodadi Ramunia - Pulungan, Maya Sari; Hadinugroho, Dwi Lindarto; Slamet, Bejo (Jurnal Ilmiah Global Education, 2024)
The Climate Village Program is a national program with a target of establishing 20,000 climate villages spread throughout Indonesia as an effort to control climate change in Indonesia. Implementation of the climate village program still requires strategies to increase the capacity for adaptation, mitigation, institutional strengthening and the number of climate villages. This research aims to analyze Proklim development strategies and priority strategies for Proklim development in Sidodadi Ramunia Village, Beringin District, Deli Serdang Regency, North Sumatra Province. The method used is qualitative with a survey approach and using SWOT and AHP analysis. This research began by identifying adaptation and mitigation actions that had been carried out by residents in Sidodadi Ramunia Village and then a Focus Group Discussion (FGD) was carried out which resulted in 3 activity targets to be developed, namely (1) Increasing the use of organic fertilizer; (2) creation of a waste bank and (3) development of other locations to be proposed as climate villages. SWOT analysis is carried out to formulate alternative strategies for each activity target whose priority will be determined through AHP analysis using the expert choice 11 application. The results of the AHP analysis show that the strategic priority in developing climate villages is increasing the use of organic fertilizer with a weight value of 0.402 and an inconsistency value of 0. 05. This research shows that to increase the use of organic fertilizer, training and direct assistance in making quality organic fertilizer is needed which can ultimately trigger the community to sort organic and inorganic waste.